2016
DOI: 10.1007/s12602-016-9218-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Recurrence of Vulvovaginal Candidiasis in Patients Undergoing Prophylactic Treatment with Probiotic and Placebo During the 6 Months

Abstract: This is a randomized, double-blind, clinical/comparative trial study, involving the recurrence of vaginal candidiasis (VVC) after initial treatment with oral fluconazole in patients undergoing prophylactic management with a probiotic and placebo for 6 months. Fifty-nine VVC patients who were diagnosed based on their history, physical examination, and culture of vaginal discharge were initially treated by a single dose of 150 mg fluconazole. According to the table of random numbers, the sample was divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
0
13
0
7
Order By: Relevance
“…1. The remaining 30 articles were included in the qualitative synthesis, including 20 studies for BV alone or with other pathogens (15-34), 10 studies for VVC alone (31,(35)(36)(37)(38)(39)(40)(41)(42)(43) and 1 study for BV/VVC (44).…”
Section: Resultsmentioning
confidence: 99%
“…1. The remaining 30 articles were included in the qualitative synthesis, including 20 studies for BV alone or with other pathogens (15-34), 10 studies for VVC alone (31,(35)(36)(37)(38)(39)(40)(41)(42)(43) and 1 study for BV/VVC (44).…”
Section: Resultsmentioning
confidence: 99%
“…Palacios et al found that there was a statistically significant, threefold reduced risk of recurrence of VVC three months after single‐dose clotrimazole therapy in women receiving vaginal L. plantarum compared to clotrimazole alone (Palacios et al, ). Other studies have similarly shown a decreased recurrence rate in patients receiving probiotics after single‐dose fluconazole therapy compared to fluconazole alone; this effect was demonstrated at 4 months with L. plantarum (Carriero et al, ), as well as at 6 months with a combination of L. acidophilus , B. bifidum and B. longum (Davar et al, ).…”
Section: Probiotics and Vvcmentioning
confidence: 86%
“…compared to clotrimazole alone(Palacios et al, 2016). Other studies have similarly shown a decreased recurrence rate in patients receiving probiotics after single-dose fluconazole therapy compared to fluconazole alone; this effect was demonstrated at 4 months with L. plantarum(Carriero et al, 2007), as well as at 6 months with a combination of L. acidophilus, B. bifidum and B. longum(Davar et al, 2016).These studies have promising results and together demonstrate that multiple strains and combinations of probiotics can provide additional benefit to antifungals in the treatment and prevention of acute VVC. However, it is difficult to draw generalizable conclusions from them due to small sample sizes and the limited quantity of studies on each probiotic.4.2 | Patients with recurrent VVCRecurrent VVC is defined as at least four episodes of acute VVC within the prior 12 months.…”
mentioning
confidence: 92%
“… 40 The efficacy of oral or vaginal Lactobacillus strains in the treatment of complicated VVC has been demonstrated in many studies, and it also lowers the possibility of recurrence. In Davar et al's study, 41 7.2% of probiotic and 35.5% of placebo groups presented with a recurrence of complicated VVC within 6 months. De Seta et al 42 evaluated the effect of probiotics combined with antifungal medication on VVC treatment.…”
Section: Antibiotics and Probiotic Therapies For Bv And Vvcmentioning
confidence: 92%